Penggunaan KIT IPA yang Dipadukan Dengan Pendekatan Hands On Untuk Meningkatkan Minds On SiswaDi Kelas VB SDN Model Terpadu Madani Palu - Hartati Karto Rifai; Andi Tanra Tellu; Sahrul Saehana (Universitas Tadulako, 2015)
The aim of this research is to describe the science learning by using science kit which is integrated to the hands on method at Year VB Elementary School SDN Model Terpadu Madani Palu. The learning was focused on main material subject of optics kits. The instruments which used on this study ; Lesson Plans, observation sheet s for teacher and student’s activities, observation sheets of Hand on and Minds on for student, pretest and posttest for action on each cycle. The results showed on cycle I, the student’s score on Mind on was 53,93 with classical average 2.45 or “start to see” with the percent of 61,28 which categorized as “good enough”. On Cycle II, the score was 79,43, average 3,61 or “ to be use to” with the percent of 90,18 which categorized as “very good”. Student’s Hand on, at Cycle I, the score was 57,27, average 2,60 or “ develop” and it was done at 65,10% and categorized as good enough whereas the cycle II showed score 78,43 average 3,56 or “ to be use to” and done at 89,13 % (very good). Teacher’s activity score on cycle I was 63, average 3,32, done 82,89% (good) and student’s activity score 75,93, average 3.45 and done 86,28% (good). Whereas on cycle II, Teacher’s activity score 70, average 3,68, done 92,90 % (very good) and student’s activity score, 82,64 (good), average 3,76, and done 93,90% (very good). For the test result of pre-action was 1633, the classical average 74, Classical absorption 74,22%, the classical complete up to 50%. On cycle I , 1836 score, classical average 83, classical absorption 83,45%, classical complete 7,27%, on cycle II, 1887 score, average 86, classical absorption 87,77 %, classical complete was 90,90%. It can be concluded that science learning by using science kit integrated to the hands on method can improve the student’s mind on at year VB Elementary school SDN Model Terpadu madani Palu.